Police Performance Against the Implementation of Investigation of Children as Perpetrators of Obscenity - Muhamad Vikram Ahmad (Universitas Negeri Gorontalo, 2021)
Abstract: This study aims to find out how the police's efforts in investigating children as perpetrators of criminal acts of obscenity and knowing the factors that hinder the police in investigating children as perpetrators of sexual abuse in Gorontalo. The type of research used in this article is empirical legal research using a qualitative approach. The results of this study indicate that the investigation of children as perpetrators of criminal acts of obscenity is regulated in Law Number 11 of 2012 concerning the Criminal Justice System for Children based on the principles of protection, justice, non-discrimination, best interests of children, respect for children's opinions, survival and growth. child development, child development and guidance, proportionality, deprivation of liberty and punishment as a last resort, and avoidance of retaliation. There are two stages of investigation of children as perpetrators of criminal acts, namely investigation, and investigation. The investigation is more directed at searching and finding events that are suspected of being criminal acts, while investigations are more directed at searching and finding evidence to arrest suspects which include summons, arrests, searches, confiscations, detentions, and examinations. Then the inhibiting factors in carrying out investigations of children as perpetrators of criminal acts of obscenity are the lack of witnesses in the obscenity case and the lack of time efficiency between the investigator and BAPAS (Penitentiary) to work together in resolving the obscenity case.